Corn Date of Planting and Depth - G. F. Sassenrath; L. Mengarelli; X. Lin (Kansas Agricultural Experiment Station Research Reports, 2020)
The exceptionally wet weather in 2019 impacted corn yield. Excessive rainfall reduced corn emergence and plant stand. Many production fields were replanted due to poor stand from flooding. In this study, corn that was planted too shallow (1 inch) or too deep (3 inches) had less yield than that planted at 2-inch depth. The best yield was observed in the corn planted on April 16, 2019. The results from this record wet year were different from previous years, when early planted corn had higher yields.
Keywords: corn planting; date of planting; depth of planting; corn maturity; cumulative growing degree days